The Contribution of Open and Distance-Learning Methodology on Custodial Rehabilitation of Prison Inmates in Kenya - Otieno, Marygorety Akinyi; Aghan, Patrick Lumumba (West African Journal of Open and Flexible Learning, 2022)
The study examined the contribution of open and distance learning methodology on the custodial rehabilitation of prison inmates in Kenya. The researcher hypothesized that open and distance learning methodology practices do not facilitate the rehabilitation of inmates in Kenyan prisons. Despite the provision of educational opportunities for inmates in Kenya, studies show that there are no effective open and distance learning strategies which enhance the rehabilitation of inmates. The study was guided by rehabilitation and lifelong theoretical frameworks (Robinson and Crow, 2009). The study employed internal and external desk research techniques. This comprised of online sources, Government of Kenya prison data and published journals. The researcher reviewed the literature on research findings on the perception and experiences of incarcerated offenders on short sentences in correctional facilities in Kenya. The study established that a significant number of correctional facilities in Kenya have not embraced the use of open and distance learning methodologies. The results further established that there was inadequate infrastructure in Kenyan correctional facilities to support the effective rehabilitation of prison inmates. The study also established that a limited number of prison staff had the requisite technical skills and competencies to supervise inmates who had an interest in participating in open and distance learning programmes. No policy framework supported the use of open and distance learning methodology in correctional facilities. The study recommends that for inmates to be rehabilitated, there is a need to strengthen the use of open and distance learning methodologies in correctional facilities.Résumé : L'étude a examiné la contribution de la méthodologie de l'apprentissage ouvert et à distance à la réadaptation des détenus dans les prisons du Kenya. Le chercheur a émis l'hypothèse que les pratiques en matière de méthodologie d'apprentissage ouvert et à distance ne facilitent pas la réinsertion des détenus dans les prisons kenyanes. Malgré les possibilités d'éducation offertes aux détenus au Kenya, les études montrent qu'il n'existe pas de stratégies efficaces d'apprentissage ouvert et à distance qui améliorent la réinsertion des détenus. L'étude a été guidée par les cadres théoriques de la réadaptation et de l'apprentissage tout au long de la vie (Robinson et Crow, 2009). L'étude a utilisé des techniques de recherche documentaire internes et externes. Il s'agissait de sources en ligne, de données sur les prisons du gouvernement kenyan et de journaux publiés. Le chercheur a passé en revue la littérature sur les résultats de recherche concernant la perception et les expériences des délinquants incarcérés pour de courtes peines dans les établissements pénitentiaires du Kenya. L'étude a établi qu'un nombre important d'établissements pénitentiaires au Kenya n'ont pas adopté la méthodologie de l'apprentissage ouvert et à distance. Les résultats ont également montré que les infrastructures des établissements pénitentiaires kenyans étaient inadéquates pour permettre une réadaptation efficace des détenus. L'étude a également établi qu'un nombre limité de membres du personnel pénitentiaire possédait les aptitudes techniques et les compétences requises pour superviser les détenus désireux de participer à un programme d'apprentissage ouvert et à distance. Il n'existe pas de cadre politique soutenant l'utilisation de la méthodologie de l'apprentissage ouvert et à distance dans les établissements pénitentiaires. L'étude recommande de renforcer l'utilisation des méthodologies d'apprentissage ouvert et à distance dans les établissements pénitentiaires afin de réhabiliter les détenus.Mots-clés : Évaluation, établissement correctionnel, évaluation du programme correctionnel, réadaptation correctionnelle, besoins criminogènes, apprentissage à distance, apprentissage ouvert.
Keywords: Assessment; correctional facility; correctional program evaluation; correctional rehabilitation; criminogenic needs; distance learning; open learning